Pengaruh Model Pembelajaran (TSTS) Melalui Lesson Study Terhadap Hasil Belajar IPA - Ni Luh Eka Swantari Dewi; Ketut Dharsana; Ndara Tanggu Rendra (Jurnal Ilmiah Sekolah Dasar, 2018)
The purpose of this study was to know significant difference of the result study in science subject between groups of students who were taught by using Two Stay Two Stray (TSTS) learning model and group of students who were not taught by using Two Stay Two Stray (TSTS) through learning model in grade V SD students in Gugus XIII Buleleng District AcademicYear 2017/2018. This research was quasy experimental. Research design was Non Equivalent Control Group Design. The population of the research was the students in fifth grade of SD in Buleleng DistrictÂ  in gugus XII on second semesterAcadmic Year 2017/2018. Samples was random sampling technique and it was obtained SD N 3 Banjar Tegal as an experimental group whichÂ  numbered16 students and SD Mutiara Penyabangan as a control group which numbered 32 students. Data collected was the test of result study in science subject which included the cognitive aspects that was obtained from result of the multiple choice / objective form. The data obtained can be analyzed inferential statistics (test - t polled variance). Based on the results showed that the average score of result study of the experimental group in science was 27.38 higher than the average score of result studyof control group that was 19.56 in mathematic. This proved that there was a significant difference of result study in science subjectbetween the students who were taught by using the Two Stay Two Stray learning model through the Study Lesson with the students who were not taught by using the Two Stay Two Stray through Lesson Study lesson in grade V SDN 3 Banjar Tegal.